2008
DOI: 10.1159/000174822
|View full text |Cite
|
Sign up to set email alerts
|

The Central Kink Region of Fowlicidin-2, an α-Helical Host Defense Peptide, Is Critically Involved in Bacterial Killing and Endotoxin Neutralization

Abstract: Fowlicidins are a group of newly identified chicken cathelicidin host defense peptides. We have shown that the putatively mature fowlicidin-2 of 31 amino acid residues possesses potent antibacterial and lipopolysaccharide (LPS)- neutralizing activities, but with a noticeable toxicity to mammalian cells. As a first step in exploring the structure-activity relationships of fowlicidin-2, in this study we determined its tertiary structure by nuclear magnetic resonance spectroscopy. Unlike the majority of cathelici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 70 publications
2
68
0
Order By: Relevance
“…As reported earlier by Xiao et al [8] and confirmed by us, M a n u s c r i p t 12 CATH-2 is resistant to salt, but C1-15 almost completely lost its antibacterial activity in the presence of 100 mM NaCl. However, we could restore the antibacterial activity in the presence of salt by Phe to Trp substitutions.…”
Section: Discussionsupporting
confidence: 78%
“…As reported earlier by Xiao et al [8] and confirmed by us, M a n u s c r i p t 12 CATH-2 is resistant to salt, but C1-15 almost completely lost its antibacterial activity in the presence of 100 mM NaCl. However, we could restore the antibacterial activity in the presence of salt by Phe to Trp substitutions.…”
Section: Discussionsupporting
confidence: 78%
“…14,15 Briefly, bacteria at the mid-logarithmic phase were washed twice in 10 mM sodium phosphate buffer, pH 7.4, diluted to 0.03 A 600 nm (equivalent to 2.5-5Â10 7 CFU ml À1 ) in the same buffer containing 1% trypticase soy broth. In a 96-well tissue culture plate, 80 ml bacteria was then mixed with native or reduced crotamine to a final concentration of 50 mg ml À1 , followed by addition of 1.5 mM of a chromogenic substrate, o-nitrophenyl-b-D-galactopyranoside (Sigma, St Louis, MO, USA), to a total volume of 100 ml per well.…”
Section: Bacterial Membrane Permeabilization Assaymentioning
confidence: 99%
“…The antibacterial activities of Fow-3(1-15), Fow-3(1-19), and Fow-3(20-27) were attenuated or even nearly lost, and Fow-3(1-15-20-27) displayed antibacterial activity similar to that of Fow-3. Fow-3 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) showed obvious cytotoxicity compared with other analogs, which demonstrated that the central hinge link (-AGIN-) was crucial to the cytotoxicity of the peptide. Fow-3 (1-15-20-27) showed good tolerance to salt ions and a considerably higher level of cell selectivity than Fow-3.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies were carried out to do this by altering certain physicochemical and structural properties, such as charge, amphipathicity, hydrophobicity, degree of structuring (␣-helix or ␤-sheet), D-isomerization, and cyclization (9,10,11,12). In addition, truncation of natural AMPs has been shown to be a simple and effective approach for the design and/or optimization of AMPs (12,13,14).…”
mentioning
confidence: 99%